Keabsahan Kontrak Sistem Administrasi Badan Hukum - Mediawati, Noor Fatimah (Universitas Muhammadiyah Sidoarjo, 2013)
Legal administrative system (sisminbakum) imposed on the environment directorate general of general legal administration (Ditjen AHU) in order to improve the function of legal services by utilizing a computer or website, such as request for approval of the company. This step is taken to overcome the inertia of the manual system. Sisminbakum service users must pay a non-tax revenues (PNBP), also must pay of charge access fees. It is the origin of alleged corruption by all relevant parties. This article explores the validity of the contract includes an agreement (contract Sisminbakum), with the assumption that if the contract is proven valid, this is not worthy of the parties concerned in it jailed. This can be understood that a contract law as the law-makers.